AN ANALYSIS OF TEACHERS’ AND STUDENTS’ PERCEPTIONS ON FORMAL AND INFORMAL ASSESSMENT: - - Nurhayati, Nurhayati; Handini, Baiq Suprapti; Fikri, Zahratul (LPPM Universitas Bumigora Mataram, 2020)
The aim of this study was to find out the teachers’ and the students’ perception about formal and informal assessment. The subject of this study was an English teacher and 30 student class of X IPS 2 at MA NW Kotaraja. The technique of collecting data was questionnaire and interview. The instruments of the data collection were questionnaire for students and interview guide for the teacher. The data were analyzed using descriptive analysis technique applying by Miles and Hubberman model. The activities of the data analysis were data reduction, data display, and conclusion drawing/verification. The results of the study showed that teachers’ perception about formal and informal assessment was a tool that help teacher to understand the students. On the other hand the students’ perception about formal and informal assessment was surprised. There were 126 (42 %) who answered Strongly Agreed which indicated they prefer formal assessment than informal assessment (Written Test). About 23 % were choose Neutral and the rest 35 % were choose Disagree and Strongly Disagree which indicated that few of the students prefer informal assessment. From the result above, it can be concluded that the majority of the students prefer formal assessment than informal assessment in getting their score.